The effect of dietary supplements on endurance exercise performance and core temperature in hot environments: A meta-analysis and meta-regression - Peel, J. S.; McNarry, M. A.; Heffernan, S. M.; Nevola, V. R.; Kilduff, L. P.; Waldron, M. (Sports Medicine, 2021)
Background: The ergogenic effects of dietary supplements on endurance exercise performance are well-established; however, their efficacy in hot environmental conditions has not been systematically evaluated. Objectives: (1) To meta-analyse studies investigating the effects of selected dietary supplements on endurance performance and core temperature responses in the heat. Supplements were included if they were deemed to: (a) have a strong evidence base for `directly` improving thermoneutral endurance performance, based on current position statements, or (b) have a proposed mechanism of action that related to modifiable factors associated with thermal balance. (2) To conduct meta-regressions to evaluate the moderating effect of selected variables on endurance performance and core temperature responses in the heat following dietary supplementation. Methods: A search was performed using various databases in May 2020. After screening, 25 peer-reviewed articles were identified for inclusion, across three separate meta-analyses: (1) exercise performance; (2) end core temperature; (3) submaximal core temperature. The moderating effect of several variables were assessed via sub-analysis and meta-regression. Results: Overall, dietary supplementation had a trivial significant positive effect on exercise performance (Hedges` g = 0.18, 95% CI 0.007-0.352, P = 0.042), a trivial non-significant positive effect on submaximal core temperature (Hedges` g = 0.18, 95% CI - 0.021 to 0.379, P = 0.080) and a small non-significant positive effect on end core temperature (Hedges` g = 0.20, 95% CI - 0.041 to 0.439, P = 0.104) in the heat. There was a non-significant effect of individual supplements on exercise performance (P = 0.973) and submaximal core temperature (P = 0.599). However, end core temperature was significantly affected by supplement type (P = 0.003), which was attributable to caffeine`s large significant positive effect (n = 8; Hedges` g = 0.82, 95% CI 0.433-1.202, P < 0.001) and taurine`s medium significant negative effect (n = 1; Hedges` g = - 0.96, 95% CI - 1.855 to - 0.069, P = 0.035). Conclusion: Supplements such as caffeine and nitrates do not enhance endurance performance in the heat, with caffeine also increasing core temperature responses. Some amino acids might offer the greatest performance benefits in the heat. Exercising in the heat negatively affected the efficacy of many dietary supplements, indicating that further research is needed and current guidelines for performance in hot environments likely require revision.